INTERVENSI FISIOTERAPI PADA IBU HAMIL DENGAN NYERI PUNGGUNG BAWAH MENGGUNAKAN INFRA RED DAN SENAM HAMIL - Sakul, Desinta; Mamuaja, Filly (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Introduction : During pregnancy, the posture of the mother's body will change. The center of gravity shifts forward, the normal lumbosacrum curve is increasingly curved and the cervico dorsal region must form a curvature (excessive anterior flexion). This is due to adjustments to the burden associated with fetal development. Increased abdominal distension makes the pelvis tilt forward, decrease abdominal muscle tone, and increase body weight, so it needs to be adjusted for pregnant women. These and other changes make musculoskeletal conditions uncomfortable, reducing the efficiency of contractions due to shifts in the center of gravity will also reduce the mechanical benefits of abdominal muscles. From this, pregnant women are risk to lower back pain. About 60% - 70% of pregnancies, estimated ± 50% of pregnant women complain of back pain. In Rurukan public health center, the prevalence of pregnant women reached 168 from December 2018 - March 2019, and 51% with low back pain. Objective : to determine the effect of infra red and pregnancy exercises in pregnant women with low back pain. Methods : case study, with respondence was 42 years old with complaints of low back pain and limited functional activities. Results: After physiotherapy intervention with infra-red and pregnancy exercises in 6 times, the results are there was a change in motion pain from 4 (severe pain) to 2 (slight pain) and examination of functional abilities using the oswestry disability index from 28% (moderate disability) to 18 % (minimum disability). Conclusion : Intervention of Physiotherapy using Infra Red and Pregnancy Exercise affect to women pregnancy with low back pain